Fugas escravas e tráfico de africanos no Rio de Janeiro, Brasil (1822-1855), com especial referência a 1829 - Medeiros Lima, Carlos Alberto; Richter Gomes, Sandro Aramis (Anuario de Historia de América Latina, 2025)
The study of slave flights in Rio de Janeiro, Brazil, can be furthered through the construction of a time series. The movement of flights was intimately connected to the slave trade, more than to any other phenomenon, and many changes affected the traffic from 1821 through 1855. An enormous growth took place during the 1820s, and a prohibition was intended in 1830-1831, with real effects during the first half of the decade. Contraband gained momentum from 1835 on, and fluctuations continued. The movement and the fluctuations of flights, as well as the characteristics of the runaways, could be understood considering the impact of the slave trade. The history of slave trade to Brazil also explains the upsurge of flights occurred in 1829, and reactions to it are also studied here. This article was developed through a massive survey of slave flights announcements published in the Diário do Rio de Janeiro and Jornal do Commercio. The analyses of such periodicals allow us to understand contemporary perceptions about the effects of the increase in captive escapes on the social life of the then Brazilian capital.